2013
DOI: 10.1007/s11302-013-9404-1
|View full text |Cite
|
Sign up to set email alerts
|

UTP-induced ATP release is a fine-tuned signalling pathway in osteocytes

Abstract: Osteocytes reside as a cellular network throughout the mineralised matrix of bone and are considered the primary mechanosensors of this tissue. They sense mechanical stimulation such as fluid flow and are able to regulate osteoblast and osteoclast functions on the bone surface. Previously, we found that ATP is released load-dependently from osteocytes from the onset of mechanical stimulation. Therefore, the aim of the present study was to investigate whether and how ATP release can be evoked in osteocytes via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 53 publications
2
30
0
Order By: Relevance
“…Previous studies on Schwann cells and osteocytes have shown that UTP can enhance the ATP e concentration [33,34]. UTP could be released together with ATP from acinar zymogen granules or from duct cells, as it has been shown for airway epithelia and astrocytoma cells [35].…”
Section: Effect Of Utp and Udp Analogues On Extracellular Atpmentioning
confidence: 90%
“…Previous studies on Schwann cells and osteocytes have shown that UTP can enhance the ATP e concentration [33,34]. UTP could be released together with ATP from acinar zymogen granules or from duct cells, as it has been shown for airway epithelia and astrocytoma cells [35].…”
Section: Effect Of Utp and Udp Analogues On Extracellular Atpmentioning
confidence: 90%
“…An early study found that the calcium signals induced by fluid flow were decreased by suramin and thapsigargin, suggesting involvement of ATP acting via P2Y receptors (Huo et al, 2008). Expression of functional P2X2, P2X7, P2Y2, P2Y4, P2Y12 and P2Y13 receptors on MLO-Y4 osteocyte-like cells has recently been described (Kringelbach et al, 2014) Several studies have also reported that osteocytes release ATP in a controlled manner (Genetos et al, 2007;Kringelbach et al, 2014;Thompson et al, 2011). This release is enhanced by UTP and mechanical stimulation and is thought to be mediated primarily by vesicular exocytosis (Kringelbach et al, 2014).…”
Section: P2 Receptors and Osteocytesmentioning
confidence: 99%
“…Expression of functional P2X2, P2X7, P2Y2, P2Y4, P2Y12 and P2Y13 receptors on MLO-Y4 osteocyte-like cells has recently been described (Kringelbach et al, 2014) Several studies have also reported that osteocytes release ATP in a controlled manner (Genetos et al, 2007;Kringelbach et al, 2014;Thompson et al, 2011). This release is enhanced by UTP and mechanical stimulation and is thought to be mediated primarily by vesicular exocytosis (Kringelbach et al, 2014). Mechanically induced ATP release can also be regulated by the α2δ1 auxillary subunit of Ttype voltage sensitive calcium channels (Thompson et al, 2011).…”
Section: P2 Receptors and Osteocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since osteocytes are embedded within bone they must be capable of preventing over-mineralisation of their lacunae (which could potentially compromise cell viability and function). ATP, which is released by all bone cells including osteocytes [22,25,[60][61][62][63][64][65], is an important source of pyrophosphate in bone [17,66]. Previous work has shown that endogenous ATP released by osteoblasts acts as an important local brake on mineralisation, an effect mediated by both purinergic signalling and the breakdown to produce pyrophosphate [38, 67,68].…”
Section: Pyrophosphate and Osteocytesmentioning
confidence: 99%